MODELING OF DIVIDEND PAYOUT, RETENTION, YIELD, CAPITAL GAINS AND IRRELEVANCE AND ITS IMPACT ON VALUE OF THE FIRM - Dr.P.Govindasamy,; Shankar, Dr.Kapila Uma; Mr.R.Ravimohan, (The journal of contemporary issues in business and government, 2021)
The organizations’ performance measured in various dimensions and one of the tricky oil of efficiency shareholders wealth maximization and this will create a momentum of growth and development. In line with this focus the impact of dividend decision is going to be verified in this paper using payout ratio, retention ratio, capital gain, dividend yield, and dividend irrelevance. While conceptualizing this, a case model has constructed in every estimation angle and the run of the outcomes helps the business and research network to include dividend decision measurement in the process of organization valuation.